Riverstar's home eaudiobook - Hunter, Erin (Warriors Super Edition, 2023)
A thrilling stand-alone adventure in Erin Hunter's #1 nationally bestselling Warriors series! In this Super Edition, discover the origins of the first leader of RiverClan—a mysterious cat whose desire for peace would help shape the dawn of the warrior Clans. When a storm-tossed river sweeps Ripple away from the park he's always known, he commits himself to the life of a peaceful loner. Still, as his new island home starts to become a sanctuary for other rogues, he can't help but feel responsible for their safety, and for the community—and Clan—they are beginning to build. But when an old friend from the park resurfaces with terrible news just as the forest cats' fights begin to escalate into bloodshed, the cat now known as Riverstar will have to decide which home he is truly committed to protecting: his new Clan or his old family. Join the legion of fans who have discovered the epic adventures, fierce warrior cats, and the wild fantasy world of the mega-bestselling Warriors series. This stand-alone entry is perfect for new readers and dedicated fans alike. Supplemental enhancement PDF accompanies the audiobook.